Study on the Influence of Family Reading Climate on Children's Reading Development - Zhu, Yunfei (International Journal of Agriculture and Food Sciences Research, 2024)
This paper explores the various components of family reading climate and their effects on children's reading habits, interests and abilities. The study shows that a good family reading climate, including a rich family book collection, a reasonable reading schedule, parents' positive reading behaviour, a comfortable reading space, reading exchanges among family members and the importance of reading, has a significant effect on children's reading habits, reading interest and reading ability. The article analyses the influence of factors such as parents’ literacy, family economic status and family life rhythm on the family reading climate, and proposes corresponding improvement strategies, such as parents’ establishment of correct reading concepts, rational planning of family reading time and space, selection of reading materials suitable for children and diversified family reading activities. The article also puts forward prospects for further research, such as studying the differences in the reading climate of families with different backgrounds and paying attention to special groups, aiming to provide references for improving the family reading climate and promoting children's reading development.